Optimizing Distribution System Operation: Integrating Multiple Battery Swapping and Charging Stations with Technical Evaluation - Guldorum, Hilmi Cihan; Diaz-Cachinero, Pablo; Munoz-Delgado, Gregorio; Contreras, Javier (IEEE, 2024)
This work presents an optimization model for a distribution system operator (DSO) to manage a distribution system (DS) that includes multiple battery swapping stations (BSSs) and charging stations (CSs). The suggested model aims to mitigate the adverse effects of electric vehicles (EVs) by minimizing the voltage drop. The DSO possesses the capability to guarantee the secure functioning of DS by managing the BSSs and CSs as necessary. Additionally, the developed model involving alternating current (AC) power flow examines voltage fluctuations and line losses. The proposed strategy prioritizes the comfort of each EV owner by taking each EV individually into account. Furthermore, multiple types of EVs are considered to guarantee an assessment of the real-world performance of the model. The model is formulated as a mixed-integer quadratically constrained programming (MIQCP) problem and solved within the General Algebraic Modeling System (GAMS) environment. Results demonstrate that even when the CSs are not under the DSO's control, utilizing batteries in the BSSs can effectively mitigate the adverse effects of EVs in addition to providing swapping service to the EVs.
Keywords: Battery-to-grid; battery swapping station; charging station; optimal power flow; vehicle-to-grid; Computer Science; Science & Technology - Other Topics; Energy & Fuels; Engineering